Teaching English in a foreign country: Legitimate peripheral participation of a native English-speaking teacher. (November 2018) - Yim, Su Yon; Ahn, Tae youn
Abstract: This study explores the participation process of an expatriate native English-speaking teacher (NEST) using legitimate peripheral participation as a conceptual lens. For this, interview data were collected from an expatriate NEST working in Korea, Bob and his co-teaching non-native English-speaking teachers (NNESTs) for an 18-month period. The results showed that the NEST's participation process led him to move away from participating fully in the local teaching community. Although the NEST initially showed his desire to become part of the community, this desire weakened when his legitimacy as a teacher was questioned and when he found himself isolated in the school system. Instead of actively contesting his positioning, the NEST found comfort in a marginalized zone where learning as a newcomer through active interaction with the members of the teaching community rarely took place. It is suggested that efforts should be made to understand the complexity of ideological and institutional factors that can affect the participation of expatriate NESTs in local teaching communities. This study seeks to provide insights into the process of NESTs' participation in co-teaching situations and suggest the need to offer more opportunities for their participation in local teaching communities.